2023
DOI: 10.3389/fphar.2023.1052301
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in peptide-based therapeutic strategies for breast cancer treatment

Abstract: Breast cancer is the leading cause of cancer-related fatalities in female worldwide. Effective therapies with low side effects for breast cancer treatment and prevention are, accordingly, urgently required. Targeting anticancer materials, breast cancer vaccines and anticancer drugs have been studied for many years to decrease side effects, prevent breast cancer and suppress tumors, respectively. There are abundant evidences to demonstrate that peptide-based therapeutic strategies, coupling of good safety and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 187 publications
(195 reference statements)
0
4
0
Order By: Relevance
“…The leading cause of cancer deaths in women is breast cancer. 30 The serum of breast cancer patients, a typical clinical bio-sample, is frequently used to deliver valuable information regarding the dynamic evolution of the human organism. Intensive investigation of glycopeptides and phosphopeptides in breast cancer serum may provide valuable details for incipient prediction and pathogenesis of breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The leading cause of cancer deaths in women is breast cancer. 30 The serum of breast cancer patients, a typical clinical bio-sample, is frequently used to deliver valuable information regarding the dynamic evolution of the human organism. Intensive investigation of glycopeptides and phosphopeptides in breast cancer serum may provide valuable details for incipient prediction and pathogenesis of breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Their ndings demonstrated that these nanoparticles signicantly improved therapy efficacy, particularly in breast cancer cases with overexpression of EGFR. 105,106 4.5.3. RNA-based therapeutics.…”
Section: Other Emerging Targeted Delivery Approachesmentioning
confidence: 99%
“…These peptides have been found in various environments, not just the gut microbiome, and serve as inspiration for gut peptide discovery efforts. Various reviews have shown how ACPs can be effective against different tumors and cancer cells (Jafari et al, 2022;Karami Fath et al, 2022;Li et al, 2023).…”
Section: Anticancermentioning
confidence: 99%
“…These peptides have been found in various environments, not just the gut microbiome, and serve as inspiration for gut peptide discovery efforts. Various reviews have shown how ACPs can be effective against different tumors and cancer cells (Jafari et al, 2022 ; Karami Fath et al, 2022 ; Li et al, 2023 ). In addition to direct inhibition of cancer cells, ACPs can also have an immunomodulatory effect as demonstrated in mouse models (Çuburu, 2022 ).…”
Section: Bioactivities Of Interestmentioning
confidence: 99%